Faktor-Faktor Berhubungan Dengan Kejadian Hipertensi Pada Nelayan Desa Titawaai Kabupaten Maluku Tengah - Windarti Rumaolat; Idham Soamole (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Hypertension is a chronic degenerative disease that many people suffer from. In several studies, coastal and fishing community groups are said to have a fairly high prevalence of hypertension when compared with other community groups. The aim of this study was to determine the factors associated with the incidence of hypertension in fishermen. This type of research is quantitative with a cross sectional design. The population in this study were all fishermen in Titawaai Village, Nusalaut District, Central Maluku Regency. Determining the sample in this study used a total sampling technique totaling 58 respondents. The research results showed that there was a relationship between sodium consumption and the incidence of hypertension with ρ value = 0.000, a relationship between smoking habits and the incidence of hypertension with ρ value = 0.002, a relationship between caffeine consumption and the incidence of hypertension with ρ value = 0.004, a relationship between stress and the incidence of hypertension with ρ value = 0.012. The conclusion of this research is that there is a relationship between sodium consumption, smoking habits, caffeine consumption and tres with the incidence of hypertension. It is recommended that existing health facilities in the community be able to improve health services by ordering them to maritime communities.